Efficiency of operator’s activity in the system remote control of unmanned aerial vehicles - Sapozhnikov, Valery O. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The effectiveness of the professional activities of the operator of an unmanned aerial vehicle complex of state aviation is characterized by its ability to perform its tasks with appropriate quality with a minimum of resources. To achieve the required efficiency in the operator’s professional activities, it is fundamentally necessary to have modern systems of professional selection and education, a scientifically based work and rest regime, a workplace that meets all the requirements of engineering psychology and ergonomics. Unification and typification of controls and information display tools will reduce both the likelihood of erroneous actions due to the negative transfer of skill, and the likelihood of losing time on adaptation to unusual or unfamiliar interfaces.
Keywords: performance; unification; typification; professional selection; interface; negative skill transfer